2014
DOI: 10.1107/s2052520614017338
|View full text |Cite
|
Sign up to set email alerts
|

XPAD X-ray hybrid pixel detector for charge density quality diffracted intensities on laboratory equipment

Abstract: The new generation of X-ray detectors, the hybrid pixel area detectors or `pixel detectors', is based on direct detection and single-photon counting processes. A large linearity range, high dynamic and extremely low noise leading to an unprecedented high signal-to-noise ratio, fast readout time (high frame rates) and an electronic shutter are among their intrinsic characteristics which render them very attractive. First used on synchrotron beamlines, these detectors are also promising in the laboratory, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The present study has demonstrated that a data correction is required for the IP reader to detect the weak reflection at this level. Several types of area detector, such as IPs, charge-coupled devices (CCD), pixel detectors etc., have been used for charge-density studies during the past couple of decades (Bolotovsky et al, 1995;Martin &Pinkerton, 1998;Wenger et al, 2014). Several types of data correction for charge-density studies, such as oblique incidence correction (Wu et al, 2002) and flat field correction (Bergamaschi et al, 2010;Thompson et al, 2011), have been developed and applied to actual data.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has demonstrated that a data correction is required for the IP reader to detect the weak reflection at this level. Several types of area detector, such as IPs, charge-coupled devices (CCD), pixel detectors etc., have been used for charge-density studies during the past couple of decades (Bolotovsky et al, 1995;Martin &Pinkerton, 1998;Wenger et al, 2014). Several types of data correction for charge-density studies, such as oblique incidence correction (Wu et al, 2002) and flat field correction (Bergamaschi et al, 2010;Thompson et al, 2011), have been developed and applied to actual data.…”
Section: Discussionmentioning
confidence: 99%
“…Re-collection and adjustment of the collection strategy to the new experimental conditions is somewhat time consuming and should be avoided if possible. With the newly introduced hybrid pixel area detectors, this contamination should no longer be problematic since these detectors are able to discriminate on photon energy and the given energy difference is most likely large enough (Wenger et al, 2014;Stalke, 2014). However, this needs to be experimentally validated.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of detector may therefore be efficiently used to isolate single X-ray bunches from the pulse train of synchrotron radiation sources in stroboscopic pumpprobe measurements (Lauhé et al, 2012;Jacques et al, 2016). We implemented a hybrid pixel detector on our laboratory diffractometer, originally for the study of electric field-induced structural changes (Fertey et al, 2013), and recently also demonstrated its excellent potential for high-resolution X-ray diffraction studies (Wenger, 2015;Wenger et al, 2014). Here, we report on the extension of this setup to laser pump/X-ray probe time-resolved crystallography in the millisecond time scale.…”
Section: Introductionmentioning
confidence: 99%